Non-Formal Islamic Education for Women Prisoner in Rumah Tahanan Negara - Hasan Asari; Saiful Akhyar Lubis; Hayatun Sabariah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The increasing number of crimes that have occurred has caused Rumah Tahanan Negara to carry out coaching activities for prisoners, especially in nonformal education. Islamic religious education is not only carried out in school institutions in Rumah Tahanan Negara education for prisoners has also been implemented, which aims to change attitudes and behavior, especially for female prisoners. This research uses a descriptive qualitative method. The data collection technique was carried out by interview, observation, and documentation, while the data analysis method used data reduction, data presentation, and verification, and conclusion. The purpose of this study was to analyze the management, material, supporting, and inhibiting factors of nonformal Islamic education for female prisoners in Rumah Tahanan Negara Klas II B Tanjung Pura Langkat. The results showed that nonformal Islamic education consisted of fostering personality and independence, eradicating literacy in the Koran, group dynamics and leadership, introduction to Islamic religious knowledge, the Islamic creed, jurisprudence, morals, and the history of Islamic culture. The supporting factors are the cooperation of various parties, the attitude of the prisoners, facilities, and the majority of Muslim women. Inhibiting factors are the lack of budget for Rumah Tahanan Negara, teaching staff, and the schedule of Islamic education.